Recurrent malignant melanoma: effect of adjuvant immunotherapy on survival. - McCulloch, P. B. (1977)
Twenty-nine patients referred consecutively to a cancer clinic because of recurrent metastatic malignant melanoma were given 5 mg of Connaught Laboratories bacillus Calmette-Guérin (BCG) by multiple cutaneous puncture at weekly and later at monthly intervals. Eight were also treated with autologous tumour vaccine and three with intralesional BCG. This group was compared with a retrospective control group of 54 patients treated with surgery and radiotherapy alone after recurrence. Prognostic features such as site of primary and of first metastasis, disease-free interval, age and sex were similar in the two groups. However, the median survival from the time of first recurrence was 12 months in the control group but 21 months in the BCG-treated group. The major improvement was in patients with disease limited to the regional lymph nodes: the median survival was 16 months in the control group but over 32 months in the BCG-treated group. Autologous tumour vaccine appeared to have no effect on survival. Serial testing of immunocompetence did not offer any prognostic advantage, although the results of some tests correleated well with extent of disease.